Galangin ameliorates experimental autoimmune encephalomyelitis in mice via modulation of cellular immunity. Issue 1 (1st January 2021) - Tan, Kok-Tong; Li, Shiming; Panny, Lauren; Lin, Chi-Chien; Lin, Shih-Chao
Abstract: Multiple sclerosis (MS) causes neurologic disabilities that effect musculature, sensory systems, and vision. This is largely due to demyelination of nerve fibers caused by chronic inflammation. Corticosteroid treatments ameliorate symptoms of MS, but do not successfully cure the disease itself. In the current study, the application of galangin, a phytochemical flavonoid extracted from the ginger family of Alpinis officinarum, on experimental autoimmune encephalomyelitis (EAE; mouse model for MS) was explored. This study investigated prophylactic and therapeutic activity of the drug and mechanisms by which it acts. The results revealed that galangin at 40 and 80 mg/kg could lower the incidence rate of MS, and alleviate clinical/pathological manifestations. Mice administered galangin presented with less limb paralysis, lower levels of inflammatory cell infiltrates, and decreased demyelination compared to vehicle controls. Levels of CD4 + IFNγ + (TH 1) and CD4 + IL-17A + (TH 17) cells in the spinal cords of EAE mice administered galangin were reduced and both cell types were not capable of expansion. More surprisingly, galangin inhibited antigen presentation and cytokine production by dendritic cells (DC). Formation of cytokines like IL-6, IL-12, and IL-23 were significantly decreased due to galangin in co-culture models of DC and T-cells. Taken together, the data lead one to conclude that galangin could potentially be used as a potent immunoregulatory agent to alleviate clinical symptoms and reduce the prevalence of MS.